Artificial intelligence in information and communication technologies, healthcare and education : a roadmap ahead - Mahalle, Parikshit N. (BOCA RATON: CRC PRESS, 2023)
"Artificial Intelligence in Information and Communication Technologies, Healthcare and Education: A Roadmap Ahead is designed as a reference text and discusses inter-dependability, communication and effective control for the betterment of services through artificial intelligence, as well as the challenges and path ahead for AI in computing and control across different domains of business and human life. The book accommodates technologies and application domains including backbone hardware, systems and methods for deployment, which help incorporating intelligence through different supervised and probabilistic learning approaches"--
Convergence of blockchain technology and artificial intelligence / Yash Navin Agarwal, Priya Yuvaraj Chougale, Varsha D. Jadhav -- Low cost single phase smart energy meter using GSM module / Rushikesh S. Tanksale, Nitin N. Sakhare, Swapnil Jadhav, Amit Samgir -- Yoga posture detection using machine learning / Pradip Mukundrao Paithane.
Includes bibliographical references and index.
Keywords: Artificial intelligence